THE WORK OF "DEVONU LUG‘OTIT TURK" AND NAMES (Scientific journal of the Fergana State University, 2024)
The article analyzes the linguistic characteristics of the toponyms used in Mahmud Koshgari's work "Devonu lug‘otit turk". As we know, this work is a valuable source that includes onomastic units, including toponymic units, belonging to the 11th century and earlier centuries. When explaining the toponyms in this work, first of all, the author paid attention to the name of the object, gave detailed information about the location, border, and which tribe lived in this place. A number of ideas such as the connection between the person who founded the place and his name and toponym, the pronunciation of the name, how it is read correctly, what other names the toponym is called among the people, increased the value of the work. In addition, the etymology of several names considered important for the field of toponymy, which tribes use topolexems in what meanings, and what other place names are involved in this lexeme are explained by Mahmud Koshghari as a powerful linguist of the era. In addition, the work explains the meanings of a number of geographical terms included in toponyms, most of which are obsolete today, and some are completely out of use. Nevertheless, many of them can be seen preserved in the existing historical place names, and at the same time, the study of such geographical terms in the source serves as a key to determining the composition and meaning of place names. Literally, the work "Devonu Lugatit Turk" is a unique treasure of the Turkic peoples, which contains a lot of unique information both for historical toponymy and, moreover, for the field of modern toponymy.